Artificial intelligence - Thomas, Peggy 1960- (Lucent library of science and technology, 2005)
A factbook on the development and uses of intelligent robots that utilize artificial intelligence.An overview of how researchers simulate brain processes in these machines, and the variety of uses the machines/robots have. Written for young adults.